Challenges and Prospects of Developing Industrial Sector in Russia in Conditions of Economic Sanctions - N. B Akulenko (Вестник Российского экономического университета имени Г. В. Плеханова)
The article describes the research dealing with trends formed in Russian industry in conditions of sanctions. Based on results of analyzing business activity of industrial enterprises factors were ranged, which limit production growth in organizations of manufacturing and mining sectors. The author revealed the impact of economic situation uncertainty on behavior of economic entities, development strategy, finance resources distribution, the level of investment activity of enterprises, as well as on the structure of finance sources of investment. In the structure of factors limiting production growth special attention was paid on home demand insufficiency, which was thoroughly studied. The author also investigated dynamics of consumer demand based on comparative assessment of retail turnover parameters, the rate of real incomes and structure of using them by the population in times of sanction introduction in 2014, 2015 and 2022. The article provides figures of the level of import-dependence in certain industries and results of pursuing policy of import-substitution. Typical problems of sectoral manufacture were identified by using the example of light industry. Distribution of entrepreneurs by fields of economic activity was analyzed and comparative analysis of sectoral structure of manufacturing enterprises in Russia and overseas countries was carried out. The author came to the conclusion that in conditions of economic sanctions in order to eliminate disproportion in industry Russia shall intensify state regulating functions and develop the system of macro-economic planning based on inter-sectoral balance.